Development of an information system for personnel management in nursing operations Ubon Ratchathani Cancer Hospital - Mantong, Santi (Journal of the Thai Medical Informatics Association, 2025)
This study aims to: 1. Examine the current situation of personnel management in the nursing department at Ubon Ratchathani Cancer Hospital. 2. Investigate the information system requirements for personnel management in the nursing department at Ubon Ratchathani Cancer Hospital. 3. Develop an information system for personnel management in the nursing department at Ubon Ratchathani Cancer Hospital. 4. Evaluate the effectiveness of the information system for personnel management in the nursing department at Ubon Ratchathani Cancer Hospital using the System Development Life Cycle (SDLC) principles. The target group consists of nursing personnel working at Ubon Ratchathani Cancer Hospital. The sample was selected using purposive sampling, including registered nurses, staff, and stakeholders involved in using the information system. The effectiveness of the system was evaluated by computer experts who are personnel from Ubon Ratchathani Cancer Hospital, holding a bachelor’s degree and having at least three years of work experience, totaling five individuals. The research tool was the information system for personnel management in the nursing department at Ubon Ratchathani Cancer Hospital, along with an assessment form for the system’s effectiveness. The statistical methods used for data analysis were mean and standard deviation. The study found that the information system for personnel management in the nursing department at Ubon Ratchathani Cancer Hospital is functional. Nursing personnel at the hospital can access personnel data according to their needs. The system consists of ten components: 1) New personnel registration system, 2) System displaying all personnel information, 3) System displaying individual personnel information, 4) Login system, 5) System for adding general/personal information, 6) System for adding educational background information, 7) System for adding meeting/training information, 8) System for adding specialized training information, 9) System for adding license renewal information, and 10) Dashboard system summarizing the number/percentage. The overall evaluation of the system’s effectiveness by experts was rated at a high level ( 4.23, SD = 0.63). References โรงพยาบาลมะเร็งอุบลราชธานี, “ประวัติโรงพยาบาลมะเร็ง อุบลราชธานี,” 2567. [ออนไลน์]. เข้าถึงได้จาก:http:// uboncancer.go.th/ubcc2016v2/abouts.php ละอองดาว ทองดี, “ระบบสารสนเทศงานนวัตกรรมสิ่ง ประดิษฐ์งานสร้างสรรค์และงานวิจัยเพื่อการประกันคุณภาพ ภายในสถานศึกษา กรณีศึกษา วิทยาลัยการอาชีพ เชียงราย,” ปริญญานิพนธ์, มหาวิทยาลัยพะเยา, พะเยา, 2557. วสันต์ เทวัญ, “การพัฒนาระบบสารสนเทศเพื่อการรับส่ง เอกสารภายในมหาวิทยาลัยเทคโนโลยีและการจัดการ กฟผ. แม่เมาะ,” ปริญญานิพนธ์, มหาวิทยาลัยพะเยา, พะเยา, 2557. เกียรติพงษ์ อุดมธนะธีระ, “วงจรพัฒนาระบบ (System Development Life Cycle: SDLC),” 2562. [ออนไลน์]. เข้าถึงได้จาก: สำนักงานโลจิสติกส์ จารุกิตติ์ สายสิงห์, “การพัฒนาระบบจัดเก็บฐานข้อมูล บุคลากรทางการศึกษาแบบ 360 องศา,” คณะศึกษาศาสตร์, มหาวิทยาลัยภาคตะวันออกเฉียงเหนือ, 2563. กัญญาภัทร จิตมาตย์, ศศิธร แสงจำรัสชัยกุล, และภิญญา สุขวิพัฒน์, “การพัฒนาระบบฐานข้อมูลศิษย์เก่าวิทยาลัย ธาตุพนม มหาวิทยาลัยนครพนม,” 2567. มนต์ชัย เทียนทอง, *สถิติและวิธีการวิจัยทางเทคโนโลยี สารสนเทศ*. กรุงเทพฯ: สถาบันเทคโนโลยีพระจอมเกล้า พระนครเหนือ, 2548. รณชัย ทิพย์มณฑา, “การพัฒนาระบบสารสนเทศเพื่อการ จัดการ สำหรับการวางแผนพัฒนาบุคลากร คณะเทคโนโลยีสารสนเทศและการสื่อสารมหาวิทยาลัยพะเยา,” 2565.